2004
DOI: 10.2308/accr.2004.79.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Balanced Scorecard: Judgmental Effects of Performance Measures Linked to Strategy

Abstract: The balanced scorecard provides a framework for selecting multiple performance measures that supplement traditional financial measures with operating measures of customer satisfaction, internal processes, and learning and growth activities. An essential aspect of the balanced scorecard lies in its articulation of the linkage between performance measures and business strategy. This study conducts an experiment to assess how individuals' evaluations of the performance of business unit managers depend on strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
243
2
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(297 citation statements)
references
References 10 publications
16
243
2
20
Order By: Relevance
“…The participants were randomly assigned to one of the three experimental conditions. In this study, the participants applied four metrics for each perspective, derived from [17,46,47].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants were randomly assigned to one of the three experimental conditions. In this study, the participants applied four metrics for each perspective, derived from [17,46,47].…”
Section: Methodsmentioning
confidence: 99%
“…Managers with limited knowledge in using SBSC types based their performance evaluations on common measures across units and ignored any unique strategy measures of each unit [17,21]. Dilla and Steinbart found that after participants had training and experience in designing SBSCs, those who were knowledgeable about the SBSC emphasized both common and unique measures [20].…”
Section: The Mediating Role Of Sbsc Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…The strategy map describes a causal relationship in a sequence. The causal chain is connected to all indicators through four balanced scorecard perspectives reflecting dynamic changes and indicating how the organization creates value [15].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, this study extends accounting research that examines the use of forward-looking and contemporaneous measures in organizations. Existing research considers how organizations use forward-looking and contemporaneous measures to: manage their businesses (Malina and Selto 2001;Hendricks et al 2004); establish relationships between forward-looking and contemporaneous results (Ittner and Larcker 1998;Bryant et al 2004); and evaluate managers' performance (Lipe and Salterio 2000;Banker et al 2004;Libby et al 2004). Other research examines how individuals use forward-looking and contemporaneous information to make decisions (Webb 2004;Kelly 2007;Farrell et al 2008).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%